Peran Leverage Sebagai Pemediasi Pengaruh Komite Audit dan Sales Growth Terhadap Tax Avoidance - Cindi Marselino; Ariefanda Iqbal Perdana; Muhsin Muhsin (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2024)
Abstract The purpose of this study is to examine the effect of the audit committee and sales growth on tax avoidance, with leverage as an intervening variable. The population in this study consists of manufacturing industries in the food and beverage sub-sector listed on the Indonesia Stock Exchange (IDX) during the years 2020-2023. The sample selection in this study used purposive sampling, resulting in a total of 57 samples from the food and beverage sub-sector manufacturing industries. The data were analyzed using Partial Least Square (PLS) with the support of the SmartPLS 4 application. The results of the study show that the audit committee has a negative effect on leverage, sales growth has a negative effect on leverage, leverage has a positive effect on tax avoidance, the audit committee has a positive effect on tax avoidance, sales growth has a positive effect on tax avoidance, leverage can mediate the effect of the audit committee on tax avoidance, and leverage cannot mediate the effect of sales growth on tax avoidance. Keywords: Audit committee; sales growth; tax avoidance; leverage.